A brushstroke with death - Blake, Bethany (Blake, Bethany. Owl & crescent mystery., 2019)
Willow Bellamy, an artist and art teacher with a magical gift for solving murders, and her owl, Rembrandt, team up with a handsome, mysterious detective to find out who killed a much despised restaurant owner.